1997
DOI: 10.1136/jnnp.62.5.501
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar atrophy and prognosis after temporal lobe resection.

Abstract: Objective-Experimental data indicate inhibitory effects of the cerebellum on seizure activity. Structural damage such as cerebellar atrophy, which is a common finding in patients with chronic epilepsy, may reduce these effects. Methods-Outcome after temporal lobectomy was studied in 78 consecutive patients, with or without cerebellar atrophy diagnosed by MRI. Results-Thirty five patients (45%) showed cerebellar atrophy. At a mean follow up of 14-6 (range, 6-40) months, 50 patients (64%) had no postoperative se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 33 publications
4
61
0
Order By: Relevance
“…25 Moreover, total cerebellectomy increased the seizure length in a study of kindled cats, and there was an association between the cerebellar volume reduction and poorer seizure control following anterior temporal lobectomy in patients with temporal lobe epilepsy. 26 Conversely, the decreased AEDs efficacy may have produced cerebellar dysfunction, resulting in cerebellar volume reduction and impaired pursuit eye movements. Prolonged seizures could evoke hypoxic-ischemic injury in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…25 Moreover, total cerebellectomy increased the seizure length in a study of kindled cats, and there was an association between the cerebellar volume reduction and poorer seizure control following anterior temporal lobectomy in patients with temporal lobe epilepsy. 26 Conversely, the decreased AEDs efficacy may have produced cerebellar dysfunction, resulting in cerebellar volume reduction and impaired pursuit eye movements. Prolonged seizures could evoke hypoxic-ischemic injury in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar atrophy is a common finding in people suffering from epilepsy, including temporal lobe epilepsy [42][43][44] , the most common form of partial epilepsy 45 and the commonest form of drug-refractory epilepsy 42 . Although the precise mechanisms are still debated, cerebellar volume reduction in people with epilepsy is often attributed to age, presence of generalized tonic-clonic seizures, duration of epilepsy, antiepileptic medication, or the seizure activity itself [42][43][44]46,47 .…”
Section: Cerebellar and Autonomic Processmentioning
confidence: 99%
“…Although the precise mechanisms are still debated, cerebellar volume reduction in people with epilepsy is often attributed to age, presence of generalized tonic-clonic seizures, duration of epilepsy, antiepileptic medication, or the seizure activity itself [42][43][44]46,47 . Specht and colleagues demonstrated in 1997 that cerebellar atrophy diagnosed by MRI was a frequent finding in surgically treated patients with temporal lobe epilepsy 44 , and concluded that increased age, presence of generalized seizures, and intellectual disability were the principal factors associated with cerebellar volume losses in their patients 44 . Botez and co-workers studied 134 adult patients with epilepsy using high-resolution CT scans, and found a higher incidence of cerebellar atrophy with longer duration of epilepsy and treatment with phenytoin 48 .…”
Section: Cerebellar and Autonomic Processmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] The cerebellar dimensions obtained in the study will be useful in clinical practice by making it possible to assess a decrease in cerebellum dimensions on radiological images between the ages of 0 and 4 years, when the cerebellum is still growing, and will also be applicable for the standardization of measurement values. The purpose of this study was therefore to obtain a database suitable for clinical use by performing cerebellar development dimension measurements in normal individuals aged 0-4 years.…”
Section: Assessment Of Cerebellar Dimensions Usingmentioning
confidence: 99%